Coordination dynamics in front crawl swimming: impacts of the environmental constraint on behavioural flexibility - Guignard, B.; Rouard, A.; Chollet, D.; Seifert, L. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
We seek to investigate the dynamics of the upper limb coordination in front-crawl swimming, manipulating the environment (i.e., classic pool vs. flume) as a function of speed increase (i.e., task constraint). Eight elite male swimmers were volunteered. They first performed 8 x 50 m bouts at 76, 80, 84, 88, 92, 96, 100 and 104% of their highest mean speed obtained on front-crawl`s 200m, and then 8 x 40 cycles at the same speeds in the flume. The stroke rate and the inter-arm coordination dynamics were recorded and computed with the help of seven inertial measurement units (IMUs; Hikob Fox, Villeurbanne, France). The swimmers` behavioural flexibility was estimated by calculating the Range of the Motor Repertoire (RMR, corresponding to maximum-minimum range of each variable). With no environment effect on the variables` dynamics, this constraint however revealed that the flume RMR reached only 61.6 and 44.7% of the values observed in the pool for Stroke Rate (SR) (F(1,7)=85.262, p=0.000, Eta=0.924) and Index of Coordination (IdC) (F(1,7)=39,417, p=0.000, Eta p2=0,849), respectively. The swimmers` behavioural flexibility was systematically more restricted in the flume for SR and IdC. Swimmers (i) had more or at least (ii) were able to more easily exploit opportunities for action to perform the task in the pool. Therefore, motor pattern adjustments seem to emerge by modulating a smaller number of degrees of freedom in the flume.